Pemetaan Kualitas Tanah dan Arahan Pengelolaan Tanah Berbasis Sistem Informasi Geografis di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - Adibya, Luh Gede Kristi; Mega, I Made; Arthagama, I Dewa Made; Trigunasih, Ni Made; Narka, I Wayan; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science, 2024)
Improving Soil Quality Mapping and Land Management Directions Using Geographic Information Systems in Pelaga Village, Petang District, Badung Regency. This study aimed to evaluate soil quality, identify limiting factors, assess soil quality distribution, and provide soil management directives in Pelaga Village, Petang District, Badung Regency. The research spanned from June to November 2023. Methodologies employed included surveys, laboratory soil analysis, and soil quality determination. Soil samples were purposively collected from homogeneous land units and composited. Physical, chemical, and biological properties were measured as soil quality indicators. QGIS 3.28 was used to map the soil quality results, and subsequent soil management recommendations were formulated. Findings revealed that soil quality varied across the study area, with very good quality observed in land units I, III, V, VI, and VII. Limiting factors included soil texture, organic carbon, nitrogen, phosphorus, cation exchange capacity (CEC), and biomass carbon. Land units IV and VIII exhibited good soil quality but with limitations such as soil texture, bulk density, CEC, organic carbon, nitrogen, phosphorus, soil pH, and biomass carbon. Moderate soil quality was noted in land unit II, with constraints including soil texture, bulk density, CEC, organic carbon, nitrogen, pH, and biomass carbon. Recommendations for soil management include the application of dolomite in SLH II, manure and urea across all SLH, ZA fertilizer in SLH IV, V, and VII, and SP-36 fertilizer in SLH I, IV, VI, VII, and VIII. Additionally, agricultural management suggestions are proposed to optimize crop production and sustainability in the study area.